2005
DOI: 10.1111/j.1473-4192.2005.00093.x
|View full text |Cite
|
Sign up to set email alerts
|

Why that, in that language, right now? Code-switching and pedagogical focus

Abstract: The study depicts the relationship between pedagogical focus and language choice in the language teaching/learning environment of English as a Foreign Language (EFL) at a Turkish university. The article presents the organisation of code‐switching which is teacher‐initiated and ‘teacher‐induced’. The data were collected from six beginner‐level English classrooms. Transcripts of the lessons were examined using the conversation analysis (CA) method of sequential analysis in relation to the pedagogical focus, appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
124
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(131 citation statements)
references
References 24 publications
6
124
0
1
Order By: Relevance
“…Many studies found that CS to students' L1 in the L2/ESL/EFL served hybrid useful functions that expand negotiation, understanding and hence interaction in the classrooms. CS in ESL classrooms might be considered an interactional resource that is used by both teachers and students in the process of reaching a native like competence in ESL/L2 (Ustunel and Seedhouse, 2005). Awad El Karim (2003) in Sudan found that, contrary to the general belief, CS is an actively positive and effective strategy in discourse.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies found that CS to students' L1 in the L2/ESL/EFL served hybrid useful functions that expand negotiation, understanding and hence interaction in the classrooms. CS in ESL classrooms might be considered an interactional resource that is used by both teachers and students in the process of reaching a native like competence in ESL/L2 (Ustunel and Seedhouse, 2005). Awad El Karim (2003) in Sudan found that, contrary to the general belief, CS is an actively positive and effective strategy in discourse.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It also emphasizes holistic and learner-centred teaching. It is not surprising then that they [13] support the importance of teacher-initiated and teacher induced code-switching and its relationship to pedagogical focus. This study set out to learn more about the perceptions of the teachers about their use of code-switching while they try to manage their classrooms.…”
Section: The Role Of Language Teachersmentioning
confidence: 99%
“…Studies found that code switching to students' L1 in the ESL classroom served hybrid useful functions that expand negotiation, understanding and hence interaction in the classrooms. Code switching in ESL classrooms might be considered an interactional resource that is used by both teachers and students in the process of understanding each other (Ustunel and Seedhouse, 2005). Awad El Karim (2003) in Sudan found that, Code switching is an actively positive and effective strategy in classroom discourse.…”
Section: Code Switching As a Communicative Strategy In Esl Classroomsmentioning
confidence: 99%